Advanced Biotechnology: Metabolically Engineered Cells for the Bio‐Based Production of Chemicals and Fuels, Materials, and Health‐Care Products. Issue 11 (11th February 2015) - Becker, Judith; Wittmann, Christoph
Abstract Corynebacterium glutamicum, Escherichia coli, and Saccharomyces cerevisiae in particular, have become established as important industrial workhorses in biotechnology. Recent years have seen tremendous progress in their advance into tailor‐made producers, driven by the upcoming demand for sustainable processes and renewable raw materials. Here, the diversity and complexity of nature is simultaneously a challenge and a benefit. Harnessing biodiversity in the right manner through synergistic progress in systems metabolic engineering and chemical synthesis promises a future innovative bio‐economy.